Novel regulation of renal gluconeogenesis by Atp6ap2 in response to high fat diet via PGC1-α/AKT-1 pathway - Akhtar, Safia (Sci Rep, 2021)
Recent studies suggested that renal gluconeogenesis is substantially stimulated in the kidney in presence of obesity. However, the mechanisms responsible for such stimulation are not well understood. Recently, our laboratory demonstrated that mice fed high fat diet (HFD) exhibited increase in renal Atp6ap2 [also known as (Pro)renin receptor] expression. We hypothesized that HFD upregulates renal gluconeogenesis via Atp6ap2-PGC-1α and AKT pathway. Using real-time polymerase chain reaction, western blot analysis and immunostaining, we evaluated renal expression of the Atp6ap2 and renal gluconeogenic enzymes, PEPCK and G6Pase, in wild type and inducible nephron specific Atp6ap2 knockout mice fed normal diet (ND, 12 kcal% fat) or a high-fat diet (HFD, 45 kcal% fat) for 8 weeks. Compared with ND, HFD mice had significantly higher body weight (23%) (P < 0.05), renal mRNA and protein expression of Atp6ap2 (39 and 35%), PEPCK (44 and 125%) and G6Pase (39 and 44%) respectively. In addition, compared to ND, HFD mice had increased renal protein expression of PGC-1α by 32% (P < 0.05) and downregulated AKT by 33% (P < 0.05) respectively in renal cortex. Atp6ap2-KO abrogated these changes in the mice fed HFD. In conclusion, we identified novel regulation of renal gluconeogenesis by Atp6ap2 in response to high fat diet via PGC1-α/AKT-1 pathway.